2016
DOI: 10.1074/jbc.m115.673129
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Characterization of Connexin41.8 and Connexin39.4, Which Are Involved in the Striped Pattern Formation of Zebrafish

Abstract: The zebrafish has a striped skin pattern on its body, and Connexin41.8 (Cx41.8) and Cx39.4 are involved in striped pattern formation. Mutations in these connexins change the striped pattern to a spot or labyrinth pattern. In this study, we characterized Cx41.8 and Cx39.4 after expression in Xenopus oocytes. In addition, we analyzed Cx41.8 mutants Cx41.8I203F and Cx41.8M7, which caused spot or labyrinth skin patterns, respectively, in transgenic zebrafish. In the electrophysiological analysis, the gap junctions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 64 publications
4
47
0
Order By: Relevance
“…S10). To determine whether cx40 inhibition changes the pigment pattern, we constructed a dominant negative form of JQ cx40 (DNcx40) by deleting six N-terminal amino acids based on the zebrafish study (25,26). Electroporation of DNcx40 into JQ embryos produced ectopic black pigmentation, consistent with results of the inhibitor experiment ( Fig.…”
Section: Melanoblast/cyte Early Marker-positive Melanocytes Reside Insupporting
confidence: 63%
See 1 more Smart Citation
“…S10). To determine whether cx40 inhibition changes the pigment pattern, we constructed a dominant negative form of JQ cx40 (DNcx40) by deleting six N-terminal amino acids based on the zebrafish study (25,26). Electroporation of DNcx40 into JQ embryos produced ectopic black pigmentation, consistent with results of the inhibitor experiment ( Fig.…”
Section: Melanoblast/cyte Early Marker-positive Melanocytes Reside Insupporting
confidence: 63%
“…5 A and B). This type of connection could be mediated with gap junction channels as seen in the pigment cells of zebrafish, where a mutant study showed that connexin is involved in stripe formation (25,26). Therefore, we set up an explant culture system in which pigment stripes form and tested the role of ion channels and gap junctions in pigment patterning.…”
Section: Melanoblast/cyte Early Marker-positive Melanocytes Reside Inmentioning
confidence: 99%
“…Double mutants for leo and luc loss-of-function alleles display a very severe phenotype, the pattern is completely dissolved with single melanophores scattered on a uniform light sheet of epithelial-like dense iridophores covered by a net of xanthophores. Mutants homozygous for the strongest of the dominant leo alleles, leo tK3 , show the same strong phenotype, arguing that both connexins can form heteromeric and homomeric gap junctions (Irion et al, 2014a; Maderspacher and Nüsslein-Volhard, 2003), which was confirmed by in vitro studies (Watanabe et al, 2015). This suggests that the communication between xanthophores and melanophores via heteromeric gap junctions provides signals to the dense iridophores to induce the transition into the loose shape required for dark stripe formation.…”
Section: Introductionmentioning
confidence: 82%
“…Several genes are autonomously required in the chromatophores for these heterotypic interactions 11,12,20,41-43 . These genes typically encode integral membrane proteins such as adhesion molecules 42 , channels 20 , or components of cellular junctions, some of which mediate direct cell contacts 43,44 . In Meox1 ( choker ) mutants, lacking the horizontal myoseptum as anatomical landmark, the horizontal orientation is lost, but stripes form of normal width and composition (Fig.…”
Section: Mainmentioning
confidence: 99%
“…In D. rerio loss-of-function mutations in the gap junction genes Cx39 . 4 ( luchs ) 44,46 and Cx41 . 8/Gja5b ( leopard ) 41,46,47 as well as mutations in Igsf11 ( seurat ) 42 , which codes for a cell adhesion molecule, lead to melanophore spots (Fig.…”
Section: Mainmentioning
confidence: 99%